An Evaluation of Vocabulary Achievement of the Students of Feeder Schools of Universitas Klabat - Ruhupatty, Nathan (JIU (Jurnal Ilmiah Unklab), 2004)
English vocabulary has expanded a lot in the past three hundred years. This expansion has not been limited only to scientific terms. There has been constant needs for new words to express concets or attitudes whichnewly emerged since of the change in communitiess have become more complex, there has also been corresponding growth in vocabulaty. This study evaluated vocabulaty achievement level of 641 second-year high school students from 12 feeder schools of Universitas Klabat. This study also sought to find out if there is significant difference in the test scores between: Students studying in SDA schools and non SDA schools, students studying in porachial schools and public schools and male and female students. The descriptive method was employed in this study. The researcher constructed his own test based on students’ English text book and the input of the resource person; he also consulted the expertise in test construction. The test was then tried out and validated. The findings of the study were proved by the statistical test of significance.